Italy : Recent Economic Developments and Selected Issues. (IMF Staff Country Reports; Country Report ;, 1997)
This paper reviews economic developments in Italy during 1995-96. The performance of the Italian economy in 1996 was characterized by a marked decline in inflation and a strengthening of the external position, accompanied however by lackluster growth. The slowdown in economic activity was more pronounced than in most European countries. Unemployment increased, albeit marginally, for the third consecutive year. The paper shows that during Italy's economic cycle in 1992-96, key macroeconomic variables did not exhibit their typical cyclical pattern. The paper also briefly reviews developments in the public finances.